The GUSC model in smart notification system: The quantitative analysis and conceptual model - Ismail S.; Suhaimi S.F.M.; Ahmad M.S. (IEEE Computer Society, 2023)
A growing interest in personal knowledge management (PKM) against personal information management (PIM) has initiated the reverse engineering process between the two concepts. PKM could be applied to the lower level knowledge hierarchy (i.e. information) to ease the understanding of explicit knowledge concept and in modeling smart devices. On the other hand, one of the common implementations of information management is in the education industry, where students experience less time to meet their lecturers to discuss their learning issues and having inefficient way to communicate via the existing learning management system. This paper investigates the communication problem between students and lecturers outside the classroom, by considering the social media usage among them. Knowing that Web 2.0 technology can be used to connect the two parties, a PKM model, which we called the GUSC model, is used to design a model of an agent-based smart notification system. This paper presents the quantitative analysis on students' GUSC pattern and their need to connect to their lecturers, in order to conceive the agent-based model. 2013 IEEE.